IJCM_244A: Awareness on breast cancer and its screening methods among the women in urban field practice area, Government Medical College, Siddipet, Telangana. - Kanmani K; Gayathry D.; Snehika A; Sreenivas G. (Wolters Kluwer Medknow Publications, 2024)
Background: Breast cancer is the most common female cancer worldwide including India, where advanced stages at diagnosis, and rising incidence and mortality rates, make it essential to understand cancer literacy in women. An understanding of the awareness and predictors of breast examination is an important first step that may guide the design of interventions aimed at raising awareness across the general population. Objective: This study aimed to evaluate the level of awareness related to breast cancer risk factors, signs, symptoms, and methods of screening among women residing in the study area. Methodology: A cross-sectional study was conducted during October 2023 - November 2023 among women residing in the urban field practice study area in Siddipet. A semi-structured questionnaire consisting of socio-demographic characteristics, questions related to awareness of breast cancer, and various screening methods was administered to 225 women in the study area. Results: The study showed an overall knowledge level of 35.00% regarding breast cancer. Participants had average knowledge about risk factors, signs, and symptoms, whereas their awareness on various screening methods was weak. Conclusion: The current study concluded that public awareness of breast cancer remains relatively low, and still needs several public awareness initiatives using mass media, such as television, Internet, and social media. Indian breast cancer patients present with advanced disease stage and have numerous poor prognostic factors, hence knowledge regarding the prevalence of risk factors was necessary. Many women, once aware, state that they would be interested in taking preventative therapy when they feel the timing is more appropriate for them. Dedicated breast health clinics, providing information about preventative therapy, and risk-reducing lifestyle changes could empower women to make personalized choices. These could be cost-effective when comparing costs of a specialist consultation with the costs of potential breast cancer therapy and psychological harm caused by breast cancer.